Mapping repertoires of collective action facing the COVID-19 pandemic in informal settlements in Latin American cities. (October 2020) - Duque Franco, Isabel; Ortiz, Catalina; Samper, Jota; Millan, Gynna
How are civil society organizations responding to COVID-19's impacts on informal settlements? In Latin America, civil society organizations have developed a repertoire of collective action, seeking to provide immediate and medium-term responses to the emergency. This paper aims to map these initiatives and identify strategic approaches to tackle the issues, given the strengths of those undertaking the initiative, and the scope, purpose and sphere of intervention. Using direct contact, a survey, and a virtual ethnography with social organizations has allowed us to identify and characterize the initiatives. The repertoire focuses on emergency measures around food security, and pedagogies for prevention, sanitation and income relief at the neighbourhood and district levels. We argue that the civil society response repertoire is diverse in form and resources but limited in scope; meanwhile the urgency of the situation and the mismatch with state action mean that crucial spheres of informality, vital to cultivating grounds for a healthy recovery phase, are being neglected.